Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To determine the original equation Michele solved, we need to determine the roots derived from the quadratic formula:
[tex]\[ x = \frac{5 \pm \sqrt{(-5)^2 - 4 \cdot 7 \cdot (-2)}}{14} \][/tex]
Start by simplifying inside the square root:
[tex]\[ x = \frac{5 \pm \sqrt{25 + 56}}{14} \][/tex]
[tex]\[ x = \frac{5 \pm \sqrt{81}}{14} \][/tex]
Since [tex]\(\sqrt{81} = 9\)[/tex]:
[tex]\[ x = \frac{5 \pm 9}{14} \][/tex]
This results in two solutions:
[tex]\[ x_1 = \frac{5 + 9}{14} = \frac{14}{14} = 1 \][/tex]
[tex]\[ x_2 = \frac{5 - 9}{14} = \frac{-4}{14} = -\frac{2}{7} \][/tex]
Now, we need to check which equation these roots satisfy among the given choices:
### Option A: [tex]\(7x^2 - 5x - 2 = -1\)[/tex]
Replace [tex]\(x\)[/tex] with 1:
[tex]\[ 7(1)^2 - 5(1) - 2 = 7 - 5 - 2 = 0 \neq -1 \][/tex]
Replace [tex]\(x\)[/tex] with [tex]\(-\frac{2}{7}\)[/tex]:
[tex]\[ 7\left(-\frac{2}{7}\right)^2 - 5\left(-\frac{2}{7}\right) - 2 = 7\left(\frac{4}{49}\right) + \frac{10}{7} - 2 = \frac{28}{49} + \frac{70}{49} - \frac{98}{49} = 0 \neq -1 \][/tex]
Option A is not correct.
### Option B: [tex]\(7x^2 - 5x + 6 = -8\)[/tex]
Replace [tex]\(x\)[/tex] with 1:
[tex]\[ 7(1)^2 - 5(1) + 6 = 7 - 5 + 6 = 8 \neq -8 \][/tex]
Replace [tex]\(x\)[/tex] with [tex]\(-\frac{2}{7}\)[/tex]:
[tex]\[ 7\left(-\frac{2}{7}\right)^2 - 5\left(-\frac{2}{7}\right) + 6 = 7\left(\frac{4}{49}\right) + \frac{10}{7} + 6 = \frac{28}{49} + \frac{70}{49} + \frac{294}{49} = \frac{392}{49} = 8 \neq -8 \][/tex]
Option B is not correct.
### Option C: [tex]\(7x^2 - 5x + 3 = 5\)[/tex]
Replace [tex]\(x\)[/tex] with 1:
[tex]\[ 7(1)^2 - 5(1) + 3 = 7 - 5 + 3 = 5 \][/tex]
Replace [tex]\(x\)[/tex] with [tex]\(-\frac{2}{7}\)[/tex]:
[tex]\[ 7\left(-\frac{2}{7}\right)^2 - 5\left(-\frac{2}{7}\right) + 3 = 7\left(\frac{4}{49}\right) + \frac{10}{7} + 3 = \frac{28}{49} + \frac{70}{49} + \frac{147}{49} = \frac{245}{49} = 5 \][/tex]
Both roots satisfy the equation.
### Option D: [tex]\(7x^2 - 5x + 5 = 3\)[/tex]
Replace [tex]\(x\)[/tex] with 1:
[tex]\[ 7(1)^2 - 5(1) + 5 = 7 - 5 + 5 = 7 \neq 3 \][/tex]
Replace [tex]\(x\)[/tex] with [tex]\(-\frac{2}{7}\)[/tex]:
[tex]\[ 7\left(-\frac{2}{7}\right)^2 - 5\left(-\frac{2}{7}\right) + 5 = 7\left(\frac{4}{49}\right) + \frac{10}{7} + 5 = \frac{28}{49} + \frac{70}{49} + \frac{245}{49} = \frac{343}{49} = 7 \neq 3 \][/tex]
Option D is not correct.
Therefore, the correct answer is [tex]\(\boxed{C}\)[/tex].
[tex]\[ x = \frac{5 \pm \sqrt{(-5)^2 - 4 \cdot 7 \cdot (-2)}}{14} \][/tex]
Start by simplifying inside the square root:
[tex]\[ x = \frac{5 \pm \sqrt{25 + 56}}{14} \][/tex]
[tex]\[ x = \frac{5 \pm \sqrt{81}}{14} \][/tex]
Since [tex]\(\sqrt{81} = 9\)[/tex]:
[tex]\[ x = \frac{5 \pm 9}{14} \][/tex]
This results in two solutions:
[tex]\[ x_1 = \frac{5 + 9}{14} = \frac{14}{14} = 1 \][/tex]
[tex]\[ x_2 = \frac{5 - 9}{14} = \frac{-4}{14} = -\frac{2}{7} \][/tex]
Now, we need to check which equation these roots satisfy among the given choices:
### Option A: [tex]\(7x^2 - 5x - 2 = -1\)[/tex]
Replace [tex]\(x\)[/tex] with 1:
[tex]\[ 7(1)^2 - 5(1) - 2 = 7 - 5 - 2 = 0 \neq -1 \][/tex]
Replace [tex]\(x\)[/tex] with [tex]\(-\frac{2}{7}\)[/tex]:
[tex]\[ 7\left(-\frac{2}{7}\right)^2 - 5\left(-\frac{2}{7}\right) - 2 = 7\left(\frac{4}{49}\right) + \frac{10}{7} - 2 = \frac{28}{49} + \frac{70}{49} - \frac{98}{49} = 0 \neq -1 \][/tex]
Option A is not correct.
### Option B: [tex]\(7x^2 - 5x + 6 = -8\)[/tex]
Replace [tex]\(x\)[/tex] with 1:
[tex]\[ 7(1)^2 - 5(1) + 6 = 7 - 5 + 6 = 8 \neq -8 \][/tex]
Replace [tex]\(x\)[/tex] with [tex]\(-\frac{2}{7}\)[/tex]:
[tex]\[ 7\left(-\frac{2}{7}\right)^2 - 5\left(-\frac{2}{7}\right) + 6 = 7\left(\frac{4}{49}\right) + \frac{10}{7} + 6 = \frac{28}{49} + \frac{70}{49} + \frac{294}{49} = \frac{392}{49} = 8 \neq -8 \][/tex]
Option B is not correct.
### Option C: [tex]\(7x^2 - 5x + 3 = 5\)[/tex]
Replace [tex]\(x\)[/tex] with 1:
[tex]\[ 7(1)^2 - 5(1) + 3 = 7 - 5 + 3 = 5 \][/tex]
Replace [tex]\(x\)[/tex] with [tex]\(-\frac{2}{7}\)[/tex]:
[tex]\[ 7\left(-\frac{2}{7}\right)^2 - 5\left(-\frac{2}{7}\right) + 3 = 7\left(\frac{4}{49}\right) + \frac{10}{7} + 3 = \frac{28}{49} + \frac{70}{49} + \frac{147}{49} = \frac{245}{49} = 5 \][/tex]
Both roots satisfy the equation.
### Option D: [tex]\(7x^2 - 5x + 5 = 3\)[/tex]
Replace [tex]\(x\)[/tex] with 1:
[tex]\[ 7(1)^2 - 5(1) + 5 = 7 - 5 + 5 = 7 \neq 3 \][/tex]
Replace [tex]\(x\)[/tex] with [tex]\(-\frac{2}{7}\)[/tex]:
[tex]\[ 7\left(-\frac{2}{7}\right)^2 - 5\left(-\frac{2}{7}\right) + 5 = 7\left(\frac{4}{49}\right) + \frac{10}{7} + 5 = \frac{28}{49} + \frac{70}{49} + \frac{245}{49} = \frac{343}{49} = 7 \neq 3 \][/tex]
Option D is not correct.
Therefore, the correct answer is [tex]\(\boxed{C}\)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.